Development of EST-SSR for preliminary analysis of genetic diversity of Cordyceps militaris. (February 2015) - Yuan, Feng; Yu, Hong; Zuo, Shimei; Adams, Alison
Abstract: Through previous research, different populations of Cordyceps militaris were determined to have varying contents of cordyceps polysaccharides and cordycepic acid, which is involved inantioxidant activity and immune stimulation. This study aimed to exploit expressed sequence tags-simple sequence repeats (EST-SSRs) and to analyse the population genetic differentiation of C. militaris . The SSR frequency of C. militaris in ESTs was 24.3%. Mono-repeats were the most abundant motif (83.4%), and the most frequent mono-repeat was A/T (98.8%). The percentage of polymorphic bands ( PPB ) of the seven populations of C. militaris ranged from 11.7% to 73.7% with a mean of 34.7%.Shannon's information index ranged from 0.0576 to 0.3021 with a mean of 0.1623. The total genetic diversity of C. militaris was 0.1907, and the genetic diversity within the population was 0.1049. The coefficient of gene differentiation was 0.4500, indicating extensive genetic differentiation of this species. The mean Nei's genetic distance among the C. militaris populations was 0.1184. The UPGMA dendrogram exhibited a low correlation between the genetic and geographic distances, which can also be confirmed by the Mantel test. The high level of diversification among populations may be due to deforestation and forest fragmentation in China. Highlights: The EST-SSRs for the Cordyceps militaris was developed. The SSRs distributing character of C. militaris was figured. C. militaris is undergoing a rapid differentiation. There was low correlation between geographic and genetic distance.